Effects of Composite Formulation on Mechanical Properties of Biodegradable Poly(Propylene Fumarate)/Bone Fiber Scaffolds - Xun Zhu; Nathan Liu; Michael J. Yaszemski; Lichun Lu (International Journal of Polymer Science)
The objective of our paper was to determine the effects of composite formulation on the compressive modulus and ultimate strength of a biodegradable, in situ polymerizable poly(propylene fumarate) (PPF) and bone fiber scaffold. The following parameters were investigated: the incorporation of bone fibers (either mineralized or demineralized), PPF molecular weight, N-vinyl pyrrolidinone (NVP) crosslinker amount, benzoyl peroxide (BP) initiator amount, and sodium chloride porogen amount. Eight formulations were chosen based on a resolution III two-level fractional factorial design. The compressive modulus and ultimate strength of these formulations were measured on a materials testing machine. Absolute values for compressive modulus varied from 21.3 to 271 MPa and 2.8 to 358 MPa for dry and wet samples, respectively. The ultimate strength of the crosslinked composites varied from 2.1 to 20.3 MPa for dry samples and from 0.4 to 16.6 MPa for wet samples. Main effects of each parameter on the measured property were calculated. The incorporation of mineralized bone fibers and an increase in PPF molecular weight resulted in higher compressive modulus and ultimate strength. Both mechanical properties also increased as the amount of benzoyl peroxide increased or the NVP amount decreased in the formulation. Sodium chloride had a dominating effect on the increase of mechanical properties in dry samples but showed little effects in wet samples. Demineralization of bone fibers led to a decrease in the compressive modulus and ultimate strength. Our results suggest that bone fibers are appropriate as structural enforcement components in PPF scaffolds. The desired orthopaedic PPF scaffold might be obtained by changing a variety of composite formulation parameters.